Electronic marketplaces: an empirical study in the UK healthcare sector. (7th February 2005) - White, Andrew; Daniel, Elizabeth
Healthcare providers are seeking to limit the significant growth in the cost of healthcare provision and are increasingly seeking to use information technology to reduce costs. In the UK in particular, a recent major government report has caused a focus on the improved use of IT in the National Health Service (NHS), including the use of electronic procurement and electronic marketplaces in order to reduce the significant amounts spent on goods and services each year. This study seeks to explore the current provision and use of electronic marketplaces in the UK healthcare sector. Interviews were carried out with managers of healthcare electronic marketplaces operating in the UK, suppliers and buyers in those marketplaces and policy makers in the NHS. The study finds that, to date, the focus of healthcare electronic marketplaces operating in the UK is on the purchasing process. A number of benefits are being realised from this, some of which may not have been expected, such as an improvement in buyer–supplier relationships.